Universally bistable shells with nonzero Gaussian curvature for two-way transition waves - Nikolaos Vasios (Nature Portfolio, 2021)
Curved elastic shells have unique mechanical behavior and multiple stable configurations, but these properties fade when the shell thickness increases. Here the authors report a strategy to realize bistable doubly curved shells with arbitrary thickness, and how to optimize the dynamic response of one-dimensional connected arrays of such doubly-curved bistable shells.